Servperf versus Servqual: Reconciling Performance-Based and Perceptions-Minus-Expectations Measurement of Service Quality - Cronin, J. Joseph; Taylor, Steven A. (Journal of Marketing, 1994)
The authors respond to concerns raised by Parasuraman, Zeithaml, and Berry (1994) about the relative efficacy of performance-based and perceptions-minus-expectations measures of service quality. They demonstrate that the major concerns voiced by these authors are supported neither by a critical review of their discussion nor the emerging literature. Several research issues relative to service quality measurement and strategic decision making also are identified.